PENGEMBANGAN ALAT PRAKTIKUM GERAK JATUH BEBAS MENGGUNAKAN SENSOR PHOTOTRANSISTOR UNTUK PEMBELAJARAN FISIKA PADA MATERI GERAK JATUH BEBAS - Maiyena, Sri; Imamora, Marjoni; Ningsih, Fitri (IAIN Batusangkar, 2017)
This study aims to produce free fall practicum tools by utilizing phototransistor sensors to record the travel time of objects that fall from the starting point to the end point. Dealing with free falling equipment (GJB), equipment in schools is generally still very simple that is using a stopwatch. This type of research is a research and development using 4-d model (define, design, develop and disseminate), which is limited to the stage of development to practicalization activities. Data were collected through validation and responses toward administered questionnaires. Data analysis were conducted by analyzing validation sheet and quantitative response questionnaire by finding percentage of each item on the validation sheet. Then the data validation results are analyzed by descriptive technique to describe the quality of the developed product. The result of calibration of free fall practicum by using phototransistor sensor at 40 cm, 50 cm, and 70 cm distance obtained the average travel time of each object is 0.28 s, 0.32 s, and 0.37 s. These results indicate that the practicum tool has been calibrated. Validation of practicum tool is 72,39% and validation of questionnaire response of practican is 75%, indicating tool categorized valid. Furthermore, this tool is tested in class X.MIA and XI.MIA MAN 3 Payakumbuh which consisted 23 students in the science laboratory of MAN 3 Payakumbuh with the questionnaire response practicality are 87.75% and 84.41% respectively which are categorized very practical.